EFFORTS AND OUTCOMES IN ENHANCING EARLY CHILDHOOD EDUCATORS’ DIGITAL LITERACY AT PAUD INSTITUTIONS - Rita Nuryanti; Sri Nurhayati; Safuri Musa; Nandang Rukanda (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Singaperbangsa Karawang, 2024)
This study investigates the efforts made by Early Childhood Care and Education (ECCE) institutions in kecamatan Sukasari, Bandung, to enhance the digital literacy of early childhood educators. Employing a qualitative approach and case study method, the research involved observations, documents study and in-depth interviews with representatives from four ECCE institutions. Data analysis was conducted through thematic analysis, a systematic method for identifying, analyzing, and reporting patterns within the data. The results indicate positive outcomes, including enhanced teaching methods, increased creativity and resourcefulness, improved student engagement and comprehension, and educators' adaptability to technological changes. This study contributes new knowledge to the field by highlighting comprehensive and dynamic strategies employed by ECCE institutions to enhance teachers' digital literacy. The findings underscore the necessity of a holistic, supportive, and adaptive approach to digital literacy in early childhood education, aligning with current research trends in the field.